2017
DOI: 10.2147/ndt.s130269
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and safety of oxcarbazepine in the treatment of children with epilepsy: a meta-analysis of randomized controlled trials

Abstract: BackgroundTo assess the efficacy and safety of oxcarbazepine (OXC) in the treatment of children with epilepsy.MethodsRandomized controlled trials (RCTs) published in PubMed, Embase, Web of Science, Cochrane Library, Scopus, SinoMed (Chinese BioMedical Literature Service System, China), and Chinese National Knowledge Infrastructure (China) database were systematically reviewed. Eligible studies were those that compared the efficacy and safety of OXC with other antiepileptic drugs in epilepsy. Risk ratio (RR) wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 26 publications
(51 reference statements)
0
14
1
Order By: Relevance
“…First, we used both VPA and LEV in this study, but VPA seems to be ineffective for cognitive function improvement. In contrast to our findings, a previous study [24] reported that VPA plays an anti-epileptic role by enhancing inhibitory neurotransmitters. Further research is needed on the effects of VPA on cognitive function.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…First, we used both VPA and LEV in this study, but VPA seems to be ineffective for cognitive function improvement. In contrast to our findings, a previous study [24] reported that VPA plays an anti-epileptic role by enhancing inhibitory neurotransmitters. Further research is needed on the effects of VPA on cognitive function.…”
Section: Discussioncontrasting
confidence: 99%
“…Sodium valproate (VPA) and levetiracetam (LEV) are extensively used anti-epileptic drugs in clinical practice, and both have satisfactory therapeutic effects and safety [22,23]. VPA plays an anti-epileptic role, mainly by enhancing the inhibitory neurotransmitter gamma aminobutyric acid (GABA) [24], and LEV plays an anti-epileptic role by combining synaptophysin with synaptic vesicle protein 2A (SV2A) [25].…”
Section: Introductionmentioning
confidence: 99%
“…The Medical Products Agency (MPA) recommends oxcarbazepine to children because of its ‘high evidence in children’ . In meta‐analysis, oxcarbazepine has been shown to be equally efficient as comparative AED with less impact on cognitive function . The increase in levetiracetam could be attributed to its generally better tolerability than conventional AEDs .…”
Section: Discussionmentioning
confidence: 99%
“…Thirteen SRs evaluated rates of seizure freedom23,26,31,37,40,41,4346,4951 (Figure 2A) and indicated that LEV increased the rates of seizure freedom compared with placebo,23,26,31,40,44,46,49,50 but there was no difference when LEV was compared with OXC,41,49 LTG23,37,45,51 and brivaracetam 40…”
Section: Resultsmentioning
confidence: 99%